CIVICS EDUCATION: ITS ROLE IN SOLVING CHARACTER PROBLEMS THAT ARISE DURING ONLINE LEARNING - Jennifer Angeline Sugiarto; Novia Azka Putri Andari; Gading Nadiyah Sari; Kezia Eunike Darmawan; Moses Glorino Rumambo Pandin (Universitas Muhammadiyah Tapanuli Selatan, 2021)
In response to the Covid-19 outbreak, the Indonesian government has issued a policy to change face-to-face learning processes into online learning processes during pandemic in an attempt to prevent and suppress the transmission of Covid-19 in Indonesia. Therefore, online learning platforms play a big role in assisting the online learning process. Unfortunately, online learning comes with a lot of problems. One of which is moral decadence among students. This article discusses the underlying factors that cause moral decadence among students, the problems resulting from online learning, and offers solutions on how to deal with those problems. This research uses qualitative approach with literature review method which includes gathering, sorting, analyzing, and concluding data from a total of 42 journal articles. To keep the relevancy, journals and articles used are only ones published between 2019-2021. The reality of these data will then be checked upon by conducting interviews with related subjects. After research, it can be concluded that these problems mainly emerge due to their inability to adapt with the change of learning process, lack of teacher and parental supervision, and technical problems. Teachers can improve the effectiveness of civic education during online learning through game-based and portfolio-based learning methods. These learning methods enable teachers and students to still have active interaction and supervision which would contribute to character building, despite the online learning system. Collaboration with the parents also helps teachers to further increase the success of civic education during online learning. However, this research is only limited to education in Indonesia and mainly focuses on the teachers’ role. Therefore, we highly recommend future researchers to conduct research on other factors which may affect students’ moral characters during online learning, such as parents’ role or social circle.